Biomembrane Protocols II. Architecture and Function - Graham, John M.; Higgins, Joan A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1994)
There have been many important advances in our understanding of biological membrane structure and function over the last decade. Much of this progress has been driven by the development of new techniques for studying membrane components and their interactions. Tradition ally, the investigation of membranes has largely occurred within the domains of biochemistry, physical chemistry, and cell biology; but many of the most significant advances have resulted from an expansion into other disciplines, such as molecular biology, immunology, and the clinical sciences. In these two volumes we have attempted to bring together some of these techniques—to combine the old and the new. Biomembrane Protocols: II. Architecture and Function is concerned exclusively with the architecture and activities of membranes, whereas the companion volume, Biomembrane Protocols: I. Isolation and Analysis, deals with their isolation and compositional analysis. The aim of each chapter is to provide detailed technical and meth odological information that will allow the reader to perform the tech nique successfully, without the need to consult other texts. Detailed reviews of membrane structure and function are not included, except where they are relevant to the choice or efficacy of a particular proce dure. In addition to Materials and Methods sections, each chapter has a Notes section that explains the reasons for taking certain steps and pro vides practical tips for applying the techniques to other systems.
Crystallization of Membrane Proteins for X-Ray Analysis -- Determination of Cell-Surface Polarity by Solid-Phase Lactoperoxidase Iodination -- Biochemical Methods to Determine Cell-Surface Topography -- Use of Antipeptide Antibodies for the Isolation and Study of Membrane Proteins -- The Production of Monoclonal Antibodies to Membrane Proteins -- Purification of a Membrane Protein (Ca2+/Mg2+-ATPase) and Its Reconstitution into Lipid Vesicles -- Measurement of Protein-Protein Interactions in Reconstituted Membrane Vesicles Using Fluorescence Spectroscopy -- Measurement of Lipid-Protein Interactions in Reconstituted Membrane Vesicles Using Fluorescence Spectroscopy -- Determination of the Transverse Topography of Membrane Lipids Using Enzymes and Covalent Labels as Probes -- Determination of the Transverse Topography of Membrane Phospholipids Using Phospholipid Transfer Proteins as Tools -- Prothrombinase Complex as a Tool to Assess Changes in Membrane Phospholipid Asymmetry -- Fluorescent Glycerolipid Probes -- Synthesis and Use of Spin-Labeled Lipids for Studies of the Transmembrane Movement of Phospholipids -- Measurement of Membrane Fluidity and Membrane Fusion with Fluorescent Probes -- Extraction and Assay of Cyclic Nucleotides -- Analysis of G-Proteins Regulating Signal Transduction Pathways -- Assay of Protein Kinases and Protein Phosphorylation -- Analysis of Cellular Phosphoinositides and Phosphoinositols by Extraction and Simple Analytical Procedures -- Analysis of Cellular Phosphoinositides and Phosphoinositols By High-Performance Liquid Chromatography -- Cytosolic Free Calcium Measurements in Single Cells Using Calcium-Sensitive Fluorochromes -- Membrane Permeabilization with Bacterial Toxins -- Measurement of Ion Fluxes and pH Gradients Across Cell Membranes -- Ligand Binding and Processing -- The Binding of Protein-Ligands to Cell-Surface Receptors.
Keywords: Cell biology; Cell Biology